"No Man Is an Island": Perspectives of CHamorus in Guam on COVID‐19. Issue 1 (24th November 2021) - Joo‐Castro, Lucy; Emerson, Amanda
Abstract: Objectives: Guam is a United States territory situated in the western Pacific Ocean with a multiethnic population numbering approximately 168, 000. The CHamorus, who are the Indigenous people of Guam, make up 37%. In this study, we sought to explore CHamorus' perspectives on and experiences of COVID‐19. Design: Interviews were conducted with 10 CHamoru adults in June‐July 2020 via telephone for a larger study on understanding how the collective history of the CHamoru people is perceived relative to contemporary health beliefs and practices. This study is a secondary data analysis of questions that focused on COVID‐19. We used thematic analysis techniques to analyze the data. Results: Three themes were identified: self and other, or "no man is an island" ; trust in government ; and focusing on the positives . A cross‐cutting theme was commitment to the common welfare of the community through interconnectedness and inafa'maolek (doing good for others). Conclusion: Results indicated that CHamorus recognized a balance between community and individual, the need to protect the vulnerable while also considering personal choice, and the implications of enforced social distancing on community and economic stability.